Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.egja.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combined ultrasound guided anterior and posterior rectus sheath block for postoperative analgesia following umbilical hernia repair: Randomized, controlled trial

Abstract: Background: Anatomical variations in the thoracic nerves T7 to T11was found in up to 30% of the population as the anterior cutaneous branch of the nerves are formed before the rectus sheath and so do not penetrate the posterior wall of the rectus sheath. Posterior rectus sheath block was found to be effective for perioperative analgesia. We tested the efficacy of addition of anterior rectus sheath block to capture the anterior cutaneous branch of intercostal nerves as they emerge from the rectus muscle in ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In line with our ndings, studies showed that BRSB is effective in reducing the severity of postoperative pain score, analgesics consumption and increases time to rst analgesic request [24][25][26][27]. While other studies failed to demonstrate BRSB effectiveness [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…In line with our ndings, studies showed that BRSB is effective in reducing the severity of postoperative pain score, analgesics consumption and increases time to rst analgesic request [24][25][26][27]. While other studies failed to demonstrate BRSB effectiveness [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…The current study has demonstrated the efficacy of adding hyaluronidase to bupivacaine in RSB that significantly lower intraoperative fentanyl consumption in group H than group B (167.75±20.6and 186.25±20.57 ug) respectively. In a study done by Ibrahim et al 13 , the authors reported that the mean intraoperative fentanyl dose was (19.23 ± 4.96 ug), (15.28 ± 2.75 ug) in the control group, and posterior rectus sheath block (PRSB) respectively(P < 0.001) 11 . Kasem & AbdelKader have reported no statistically significant difference between the R group (RSB) and the L (local infiltration) group concerning the total amount of fentanyl consumption intraoperatively (168 ± 28 and 174 ± 36 μg, respectively) 14 .…”
Section: Discussionmentioning
confidence: 98%
“…Bilateral posterior RSB is used for postoperative pain control, including laparoscopy, umbilical hernia, pediatric, and gynecological surgery. It provides dense and predictable analgesia over the central area of the ventral abdominal wall from the xiphisternum to the symphysis pubis 13 . Recently many studies have searched the effect of adding hyaluronidase to the different local anesthetic mixtures as an adjuvant in some regional blocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral RSB is used to reduce postoperative pain after laparoscopic, pediatric, gynecological, and umbilical hernia surgery. It gives better analgesia over the core portion of the ventral abdominal wall from the xiphisternum to the symphysis pubis [11] . There were differences in age, sex, and weight across the groups, but they were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%